(untitled) (International Journal of Food and Nutritional Sciences, 2026)
Even teachers who believe in inclusive education may struggle to practise it if they doubt their own ability to teach children with disabilities. Self-efficacy—a person’s belief in their capacity to carry out the actions required to achieve a goal—has emerged as a key determinant of how confidently and persistently teachers engage in inclusive practice. The present study assessed the self-efficacy of teachers for teaching children with disabilities in inclusive settings and examined its relationship with their attitudes towards inclusion as well as its variation by teaching experience and training. A descriptive and correlational survey design was adopted, and data were collected from 200 teachers through a standardised teacher-efficacy scale together with an attitude measure. The findings show that teachers report moderate self-efficacy for inclusive practice, strongest in managing behaviour and weakest in using specialised instructional strategies. Self-efficacy was significantly and positively correlated with attitudes towards inclusion, and was significantly higher among trained and more experienced teachers. The study concludes that building teachers’ self-efficacy—through training, experience, and support—is essential to translate positive attitudes into effective inclusive teaching, and it offers recommendations accordingly.